(untitled) (Research, Society and Development, 2020)
Objective: evaluate the results of the P300 potential in individuals diagnosed with Central Auditory Processing Disorder, before and after the Acoustically Controlled Auditory Training. Methods: Observational, descriptive and longitudinal study. Five children from eight to 14 years old participated in the study. The evaluation and reassessment of the central auditory processing and P300 was performed before and after the application of the Acoustic Controlled Auditory Training program. Results: A descriptive analysis of data on preand post therapeutic measures was performed. There was na improvement in the auditory mechanisms, mainly monoaurals with low redundancy and dichotic. It was observed that of the Five patients evaluated, four had increased amplitude and in three there were changes in P3 latency, with a reduction in the values ​​obtained before and after auditory training. Conclusion: It is possible to observe changes in the P300 potential parameters resulting from neural plasticity after Acoustically Controlled Auditory Training, demonstrating the importance of using objective and behavioral measures to monitor the therapeutic process.